2018
DOI: 10.1016/j.copsyc.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding physical health problems in personality disorders

Abstract: Personality disorders are associated with a range of adverse health outcomes, contributing to the high healthcare utilization seen in patients with these disorders. A growing literature supports a robust association of personality disorders and health problems. The primary aim of this article is to summarize the most recent research documenting the associations between personality disorders and health conditions. Extending past reviews, we discuss the association of personality disorders with chronic physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
(66 reference statements)
1
39
1
Order By: Relevance
“…Personality disorder (PD) affects up to 10% of the general population and is associated with considerable burden to individuals, their families and wider society. Individuals with the diagnosis of PD experience significantly poorer general health compared to their counterparts in the general population . This exacts a heavy toll over the life course, and it has recently been reported that people with diagnosed PD have considerably shortened lives with premature deaths resulting from both natural and unnatural causes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality disorder (PD) affects up to 10% of the general population and is associated with considerable burden to individuals, their families and wider society. Individuals with the diagnosis of PD experience significantly poorer general health compared to their counterparts in the general population . This exacts a heavy toll over the life course, and it has recently been reported that people with diagnosed PD have considerably shortened lives with premature deaths resulting from both natural and unnatural causes .…”
Section: Introductionmentioning
confidence: 99%
“…Although a growing pool of studies report associations between PD and a range of physical illnesses , to our knowledge, there has not yet been a longitudinal investigation of the associations between PD and the full range of physical disorders responsible for hospitalisation. Such an investigation is much needed in understanding the use of medical resources in the population beyond mental health care .…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this review found that, compared to controls, people diagnosed with Cluster B PDs were at increased risk of experiencing syncope, seizures and arthritis, as well as elevated levels of health concern in general [8]. It was also noted that people with PD experience faster annual rates of health decline (by 50%) from adolescence to their mid-30 s compared to controls [8]. These health problems 1 3…”
Section: Introductionmentioning
confidence: 93%
“…This loss of life years cannot simply be attributed to excess rates of suicide [6,7]. A recent review of the literature relating to physical health problems experienced by people with PD has summarised associations with pain conditions, obesity and chronic illnesses including CVDs [8]. The authors of this review found that, compared to controls, people diagnosed with Cluster B PDs were at increased risk of experiencing syncope, seizures and arthritis, as well as elevated levels of health concern in general [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation